Attitudes and perspectives of 534 Chinese pediatricians toward internet hospitals - Cui, Wenbin; Zhu, Weijun; Li, Xiaojie; Wu, Danmai; He, Ping; Yu, Guangjun (Frontiers in Pediatrics, 2022)
Background: Internet hospitals introduced in China have effectively reduced service time and space, promoted high-quality pediatric medical resources to grassroots areas, solved the contradiction between supply and demand of pediatric medical resources, and met patients’ increasing multi-level and diversified medical service needs. However, pediatricians' attitudes toward and satisfaction with the use of internet hospitals remain unknown. Objective: This study aimed to investigate pediatricians' knowledge of, use of, and satisfaction with internet hospitals in order to identify major issues in internet hospital development, and to understand pediatricians' attitudes and opinions on the construction, development and use of internet hospitals. Methods: A total of 625 pediatricians in 17 public tertiary hospitals in Shanghai were surveyed from November 1-30, 2021. 534 pediatricians completed the survey, and the response rate was 85.44%. Pediatricians’ baseline demographic data were collected and information about their use of and satisfaction with internet hospitals. Results: About 70.22% (375/534) of pediatricians knew about internet hospitals and about 54.68% (292/534) use internet hospitals for patient consultation, diagnosis, and treatment. Utilized services mainly focused on online consultation (271/292, 92.81%), online follow-up consultation (174/292, 59.59%), and health sciences (111/292, 38.01%). Online services were provided by 69.18% (202/292) of pediatricians for less than 1 hour a day, and 75.00% (219/292) responded to fewer than five patient consultations online every day. Pediatricians' overall satisfaction with internet hospitals was low (3.59±0.92 points), user experience, systems functions, operation processes, service prices and performance rewards of internet hospitals were main influencing factors. Pediatricians are enthusiastic about further development of internet hospitals, with 87.83% (469/534) willing to provide services on the internet hospital platform. Conclusions: Most pediatricians view internet hospitals favorably and are eager to contribute to the development of online diagnosis and treatment services. The development of internet hospitals will be more strongly supported by improving pediatricians' satisfaction and mobilizing their enthusiasm and initiative to participate in internet medical services.